Degradable cellulose esters

By adding alkaline materials and enzyme materials to the cellulose ester to form coatings or pills, the problem of slow degradation of cellulose ester materials is solved, and rapid degradation and environmentally friendly results are achieved.

CN119859194APending Publication Date: 2025-04-22ACETATE INTERNATIONAL LLC

Patent Information

Application Number
CN202510088654.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-02-10
Filing Date
2021-02-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing cellulose ester materials, especially cellulose acetate, degrade slowly, resulting in environmental pollution, and existing improved methods fail to effectively shorten the degradation time and maintain the performance of cigarette filters.

Method used

The coating or pill is formed by adding alkaline material, enzyme material or a combination thereof to the cellulose ester to promote the degradation of the cellulose ester. Alkaline and enzyme materials can rapidly hydrolyze cellulose acetate upon exposure to water, reducing its substitution, thereby accelerating the degradation process.

Benefits of technology

The rapid degradation of cellulose ester materials is achieved, the degradation time is shortened to 20 days or less, and the degraded material is close to neutral, reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859194A_ABST
    Figure CN119859194A_ABST
Patent Text Reader

Abstract

A degradable cellulose ester is disclosed herein. The cellulose esters may be formed as tows for cigarette filters or as articles, such as molded articles. A basic material, an enzyme material, or a combination thereof is included in the cellulose ester to degrade the cellulose ester.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application with a filing date of February 10, 2021, application number 202180009633.7, and invention name “Degradable Cellulose Ester”.

[0002] Priority claim

[0003] This application claims priority to U.S. Provisional Application No. 62 / 972,621, filed on February 10, 2020, the entire contents and disclosure of which are incorporated herein by reference. Technical Field

[0004] The present invention generally relates to a method for degrading cellulose esters such as cellulose acetate by adding an alkaline material, an enzyme material, or a combination of an alkaline material and an enzyme material to the cellulose ester. In particular, the present invention relates to including coated alkaline materials and / or enzyme materials in cellulose ester tows or articles. Background Art

[0005] Cellulose esters are widely used for many purposes, including for molded articles and as cellulose acetate tow in cigarette filters. Although cellulose esters (such as cellulose acetate) are known biopolymers that degrade, the degradation rate is slower than that of natural cellulose. For example, cigarette filters may take up to 15 years to degrade because cellulose acetate will not degrade until enough acetyl groups are removed to allow the microbial recognition material to degrade. After smoking, filters are often discarded in the environment and are one of the most common forms of man-made garbage in the world. It is estimated that 4.5 trillion cigarette filters become garbage every year. Due to the degradation time of cellulose acetate and the plasticizers contained in the filter, garbage retention is longer than expected. Although attempts have been made to form biodegradable filters containing cellulose acetate, these attempts have not been successful due to a variety of reasons, including undesirable changes in cigarette taste due to modification and / or additives and insufficient shortening of the degradation time. Molded articles made of cellulose esters are subject to similar defects.

[0006] U.S. Patent No. 5,084,296 (incorporated herein by reference) discloses a composition comprising cellulose acetate or other cellulose esters and anatase titanium oxide having (1) not less than 30 m 2 / g specific surface area, (2) 0.001 to 0.07 μm primary particle size, or (3) not less than 30 m2 / g specific surface area and 0.001 to 0.07 μm primary particle size. In order to improve photodegradability and dispersibility, the surface of titanium oxide can be treated with phosphates or other phosphorus compounds, polyols, amino acids or others. The use of low-substituted cellulose esters with an average degree of substitution not exceeding 2.15 ensures high biodegradability. The composition may further contain a plasticizer and / or an aliphatic polyester, a biodegradation promoter (e.g., an organic acid or its ester). The degradable cellulose ester composition is highly photodegradable and moldable, and can therefore be used to manufacture various articles.

[0007] U.S. Patent No. 8,397,733 (incorporated herein by reference) discloses a degradable cigarette filter comprising a filter element of expanded cellulose acetate tow and a plug wrap surrounding the filter element, and pellets dispersed in the tow. The pellets include a material suitable for catalyzing the hydrolysis of the cellulose acetate tow, which is encapsulated by an inner layer of a water-soluble or water-permeable material and an outer layer of cellulose acetate having a DS in the range of 2.0-2.6.

[0008] U.S. Patent Publication No. 2009 / 0151738 (incorporated herein by reference) discloses a degradable cigarette filter comprising a filter element of expanded cellulose acetate tow, a filter plug wrap surrounding the filter element, and a coating or pellet in contact with the tow. The coating and / or pellet may be composed of a material suitable for catalyzing the hydrolysis of the cellulose acetate tow and a water-soluble matrix material. The material may be an acid, an acid salt, an alkali, and / or bacteria suitable for producing an acid. The coating may be applied to the tow, the filter plug wrap, or both. The pellet may be placed in the filter element. When water contacts the water-soluble matrix material, the material suitable for catalyzing the hydrolysis is released and catalyzes the hydrolysis and subsequent degradation of the cellulose acetate tow. The foregoing also applies to articles made of cellulose esters.

[0009] Therefore, there is a need for the controlled and sustained release of materials that aid in the degradation of cellulose esters used in articles and cigarette filters. Summary of the invention

[0010] In some aspects, the disclosure relates to a degradable cellulose ester product comprising a cellulose ester having a degree of substitution greater than 1.3, wherein at least a portion of the product comprises an alkaline material, an enzyme material, or a combination thereof. Cellulose esters may include cellulose acetate, cellulose butyrate, cellulose propionate, cellulose triacetate, cellulose acetate propionate, cellulose acetate butyrate, cellulose propionate butyrate, cellulose nitrate, cellulose sulfate, cellulose phthalate, and a combination thereof. In some aspects, an alkaline material, an enzyme material, or a combination thereof may be provided as a coating on a cellulose ester product. In other aspects, an alkaline material, an enzyme material, or a combination thereof may be provided as a pellet within a degradable cellulose ester product. The pellet may include a coating. The pH of the alkaline material may be at least 7.4, preferably at least 7.6. The alkaline material may include at least one of calcium oxide, calcium hydroxide, magnesium hydroxide, magnesium oxide, or a combination thereof. The pellet may include an alkaline material and an enzyme material, and wherein the enzyme material includes an esterase, a cellulase, a glucosidase, or a combination thereof. The enzyme material may include an esterase. The coating of the pellet may include an alkaline material. The pill may include an enzyme material, and the enzyme material may be coated with a second coating material. The pill may include an enzyme material, the enzyme material including an esterase and at least one of a cellulase, a glucosidase, or a combination thereof. The coating material may have a water solubility of at least 0.01 g / 100 mL at 25° C. The coating material may include gelatin, polyethylene glycol, polylactic acid, polycaprolactone, polyvinyl pyrrolidone, polyvinyl alcohol, or a combination thereof. The coating material may include an oligosaccharide, a monosaccharide, a polyhydroxyalkanoate, or a combination thereof. The coating material may not contain cellulose acetate. The second coating material may include gelatin, polyethylene glycol, polylactic acid, polycaprolactone, polyvinyl pyrrolidone, polyvinyl alcohol, or a combination thereof. The second coating material may include an oligosaccharide, a monosaccharide, and / or a polyhydroxyalkanoate. The pill, when exposed to water, may deacetylate the expanded cellulose acetate tow by at least 20%, preferably at least 30%, and more preferably at least 60% in 20 days or less.

[0011] In some aspects, the present disclosure relates to a degradable cigarette filter, comprising: a filter element comprising expanded cellulose acetate tow, wherein the degree of substitution (DS) of the cellulose acetate is greater than 1.3; a pellet dispersed in the expanded cellulose acetate tow; and a filter plug wrap at least partially surrounding the filter element; wherein the pellet comprises a coating and at least one of an alkaline material, an enzyme material, or a combination thereof, and wherein the pellet deacetylates the expanded cellulose acetate tow by at least 10% in 20 days or less when exposed to water. The water solubility of the alkaline material is less than the water solubility of the coating. The pH of the alkaline material may be at least 7.4, preferably at least 7.6. The alkaline material may include at least one of calcium oxide, calcium hydroxide, magnesium hydroxide, magnesium oxide, or a combination thereof. The pellet may contain an alkaline material and an enzyme material, and wherein the enzyme material includes an esterase, a cellulase, a glucosidase, or a combination thereof. The enzyme material may include an esterase. The coating may have a thickness of from 0.1 to 100 μm. The size of the pellet on its maximum diameter may be from 1 to 10 mm. The coating of the pill may include an alkaline material. The pill may include an enzyme material, and wherein the enzyme material is coated with a second coating material. The pill may include an enzyme material, the enzyme material including an esterase and at least one of a cellulase, a glucosidase, or a combination thereof. The water solubility of the coating material at 25°C may be at least 0.01 g / 100 mL. The coating material may include gelatin, polyethylene glycol, polylactic acid, polycaprolactone, polyvinyl pyrrolidone, polyvinyl alcohol, or a combination thereof. The coating material may include an oligosaccharide, a monosaccharide, a polyhydroxyalkanoate, or a combination thereof. The coating material may be free of cellulose acetate. The second coating material may include gelatin, polyethylene glycol, polylactic acid, polycaprolactone, polyvinyl pyrrolidone, polyvinyl alcohol, or a combination thereof. The second coating material may include an oligosaccharide, a monosaccharide, and / or a polyhydroxyalkanoate. The pill, when exposed to water, may deacetylate the expanded cellulose acetate tow by at least 20%, preferably at least 30%, and more preferably at least 60% in 20 days or less.

[0012] In some aspects, the present disclosure relates to a degradable cellulose acetate tow, wherein the degree of substitution of the cellulose acetate tow is greater than 1.3, and wherein the cellulose acetate tow further comprises pellets dispersed in the cellulose acetate tow, wherein the pellets comprise a coating and at least one of an alkaline material, an enzyme material, or a combination thereof, and wherein the pellets, when exposed to water, deacetylate the cellulose acetate tow by at least 10% in 20 days or less.

[0013] In some aspects, the disclosure relates to a method for forming a degradable cellulose acetate tow, the method comprising: a) providing a cellulose acetate tow having a degree of substitution greater than 1.3; b) dispersing a pellet in the cellulose acetate tow, wherein the pellet comprises at least one of an alkaline material, and an enzyme material, or a combination thereof, wherein the pellet, when exposed to water, deacetylates the cellulose acetate tow by at least 10% in 20 days or less. The pellet can hydrolyze acetate moieties within the cellulose acetate tow and cleave glycosidic bonds.

[0014] In some aspects, the present disclosure relates to a method for forming a degradable cellulose ester article, the method comprising: a) providing a cellulose ester having a degree of substitution greater than 1.3; b) dispersing pellets in the cellulose ester, wherein the pellets comprise at least one of an alkaline material, and an enzyme material, or a combination thereof, wherein the pellets, when exposed to water, deacetylate the cellulose ester by at least 10% in 20 days or less.

[0015] In some aspects, the present disclosure relates to a method for forming a degradable cellulose ester article, the method comprising: a) forming a cellulose ester article from a cellulose ester having a degree of substitution greater than 1.3; and b) providing a coating on at least a portion of the cellulose ester article, wherein the coating comprises an alkaline material, an enzyme material, or a combination thereof.

[0016] In some aspects, the present disclosure relates to a method for forming a degradable cellulose ester article, the method comprising: a) providing a cellulose ester having a degree of substitution greater than 1.3; b) providing an alkaline material, an enzyme material, or a combination thereof; and c) forming the cellulose ester article by at least one of extrusion, thermoforming, blow molding, 3D printing, injection molding, and a combination thereof. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The invention will be better understood in view of the attached non-limiting drawings, in which:

[0018] Figure 1 Test results for overall degradation according to the present disclosure are shown.

[0019] Figure 2 Additional test results for overall degradation according to the present disclosure are shown.

[0020] Figure 3 Additional test results for overall degradation according to the present disclosure are shown.

[0021] Figure 4 Yet further test results of overall degradation according to the present disclosure are shown. DETAILED DESCRIPTION

[0022] introduction

[0023] The present disclosure relates to forming a biodegradable cellulose ester from a cellulose ester having a degree of substitution greater than 1.3 by using an alkaline material, an enzyme material, or a combination thereof. In some aspects, the present disclosure relates to a cellulose ester product, wherein the alkaline material, the enzyme material, or a combination thereof is included as a coating on the cellulose ester product. In other aspects, the present disclosure relates to forming a portion of a cellulose ester product from an alkaline material, an enzyme material, or a combination thereof. In yet another aspect, the present disclosure relates to including a pill comprising an alkaline material, an enzyme material, or a combination thereof in a cellulose ester product.

[0024] The present disclosure also relates to providing a pellet in a cellulose acetate tow having a degree of substitution greater than 1.3 to degrade the cellulose acetate tow. In some aspects, the pellet is included in a degradable cigarette filter formed from the cellulose acetate tow.

[0025] Regardless of whether a pellet, coating, or portion of a cellulose ester article formed from an alkaline material, an enzyme material, or a combination thereof is used, the degradable cellulose acetate tow or cellulose ester article degrades by at least 10% in 20 days or less.

[0026] In addition to at least 10% partial degradation, the degradable tow, filter and article described herein have a total degradation value of more than 80%, such as more than 85%, more than 90%, or even more than 95%. This total degradation allows cellulose acetate or other cellulose esters to degrade like cellulose, and once the articles are degraded into cellulose, it is possible to recycle these articles. According to ISO19679 (2016), the total degradation can be measured by measuring the mg CO2 production.

[0027] As explained in the background section, it has been proposed to include pellets in cellulose acetate tow, but those methods have limitations and are only proposed for cigarette filters rather than for a wider class of cellulose ester products. The basic mechanism of cellulose ester degradation depends on the degree of substitution ("DS") of the cellulose ester. The DS of a cellulose ester refers to the degree of substitution and can be measured by ASTM 871-96 (2010), for example, for cellulose acetate. When the DS of cellulose acetate is greater than 1.3, the cellulose acetate is not degraded by naturally occurring enzymes or bacteria due to the presence of acetate moieties. In order to replace the acetate moieties with hydroxyl moieties and thereby reduce the DS, the cellulose acetate is hydrolyzed. The hydrolysis of the acetyl moieties is also referred to as deacetylation. The DS of the degradable cigarette filter described herein is typically greater than 1.3, often in the range of 2.0 to 2.6. The filter includes a filter element comprising puffed cellulose acetate tow, pellets dispersed in the puffed cellulose acetate tow, and a filter plug wrap at least partially surrounding the filter element. The pellets may include at least one of an alkaline material, an enzyme material, or a combination thereof. The pellets, when exposed to water, can deacetylate expanded cellulose acetate tow by at least 10% in 20 days or less. The alkaline material and / or enzyme material can be added in various amounts as described herein, including on a weight percent basis or on a mg basis. As further described in the examples, the alkaline material and / or enzyme material can be added in an amount from 0.1 to 50 mg, such as from 1 to 40 mg, from 5 to 40 mg, from 5 to 30 mg, from 5 to 20 mg, or any value or range therebetween. Thus, the filters described herein degrade faster than other known cellulose acetate tow filters.

[0028] Cellulose esters

[0029] As described herein, the disclosure relates to cellulose esters such as cellulose ester products, cellulose acetate tows, or cigarette filters formed by cellulose acetate tows, including alkaline materials, enzyme materials, or combinations thereof. Alkaline materials, enzyme materials, or combinations thereof are included in cellulose esters to hydrolyze cellulose esters and help degrade. As used herein, cellulose acetate refers to cellulose diacetate, although the pills and methods described herein can be used for other types of cellulose esters, including cellulose triacetate, cellulose propionate, cellulose acetate propionate, cellulose butyrate, cellulose acetate butyrate, cellulose propionate butyrate, cellulose nitrate, cellulose sulfate, cellulose phthalate, and combinations thereof.

[0030] Cellulose esters can be prepared by known methods, including those disclosed in US Pat. No. 2,740,775 and US Publication No. 2013 / 0096297, the entire contents of which are incorporated herein by reference. Typically, acetylated cellulose is prepared by reacting cellulose with an acetylating agent in the presence of a suitable acidic catalyst and then deesterifying.

[0031] Cellulose can come from a variety of materials, including cotton linters, softwoods, or hardwoods. Softwood is a general term typically used to refer to wood from conifers (i.e., conifers from the order Pinus pinaster). Trees that produce softwood include pine, spruce, cedar, fir, larch, Douglas fir, hemlock, cypress, redwood, and yew. In contrast, the term hardwood is typically used to refer to wood from broadleaf or angiosperm trees. The terms "softwood" and "hardwood" do not necessarily describe the actual hardness of the wood. However, on average, hardwoods are denser and harder than softwoods, but there is considerable variation in the actual hardness of the wood in these two groups, and some softwood trees can actually produce harder wood than wood from hardwood trees. One feature that distinguishes hardwood from softwood is the presence of pores or vessels in hardwood trees, which are absent in softwood trees. At a microscopic level, softwood contains two types of cells, namely longitudinal wood fibers (or tracheids) and transverse ray cells. In softwoods, water transport within the tree is through tracheids rather than pores as in hardwoods. In some aspects, hardwood cellulose is preferred for acetylation.

[0032] Acylating agent can comprise carboxylic acid anhydride (or simply acid anhydride) and carboxylic acid halide, particularly carboxylic acid chloride (or simply acid chloride).Suitable acid chloride can comprise, for example, acetyl chloride, propionyl chloride, butyryl chloride, benzoyl chloride and similar acid chloride.Suitable acid anhydride can comprise, for example, acetic anhydride, propionic anhydride, butyric anhydride, benzoic anhydride and similar acid anhydride.Also can use the mixture of these acid anhydrides or other acylating agents, so that different acyl groups are introduced into cellulose.In certain embodiments, mixed acid anhydride, for example acetic propionic anhydride, acetic butyric anhydride etc. also can be used for this purpose.

[0033] In most cases, cellulose is thoroughly acetylated with an acetylating agent to produce a derivatized cellulose having a high degree of substitution (DS) value (e.g., from 2.4 to 3), and in some cases some additional hydroxyl substitution (e.g., sulfate). Exhaustively acetylation of cellulose refers to an acetylation reaction that is driven toward completion such that as many hydroxyl groups as possible in the cellulose undergo the acetylation reaction.

[0034] Suitable acidic catalysts for promoting the acetylation of cellulose usually contain a mixture of sulfuric acid or sulfuric acid and at least one other acid. Other acidic catalysts that do not contain sulfuric acid can be used to promote acetylation reaction similarly. In the case of sulfuric acid, at least some of the hydroxyl groups in the cellulose can become initially functionalized as sulfates during the acetylation reaction. Once thoroughly acetylated, cellulose is subjected to a controlled partial deesterification step (usually in the presence of a deesterifying agent), which is also referred to as a controlled partial hydrolysis step.

[0035] As used herein, deesterification refers to a chemical reaction in which one or more ester groups of an intermediate cellulose ester are broken from cellulose acetate and replaced with hydroxyl groups, producing a cellulose acetate product having a (second) DS of less than 3. As used herein, a "deesterifying agent" refers to a chemical reagent capable of reacting with one or more ester groups of cellulose acetate to form hydroxyl groups on the intermediate cellulose ester. Suitable deesterifying agents include low molecular weight alcohols such as methanol, ethanol, isopropanol, amyl alcohol, R-OH (wherein R is a C1 to C20 alkyl), and mixtures thereof. Water and mixtures of water and methanol can also be used as deesterifying agents. Typically, most of these sulfates are broken during a controlled partial hydrolysis process for reducing the amount of acetyl substitution. The reduced degree of substitution can be in the range of from 0.5 to 3.0, for example from 1.3 to 3, from 1.3 to 2.9, from 1.5 to 2.9, or from 2 to 2.6. For the purposes of this disclosure, the degree of substitution is typically from 1.3 to 2.9, because below 1.3, natural degradation may occur. The degree of substitution may be selected based on the at least one organic solvent used in the binder composition. For example, when acetone is used as the organic solvent, the degree of substitution may range from 2.2 to 2.65.

[0036] The number average molecular weight of cellulose ester can be from 30,000amu to 100,000amu, for example, from 50,000amu to 80,000amu range, and can have from 1.5 to 2.5, for example, from 1.75 to 2.25 or from 1.8 to 2.2 polydispersity.Unless otherwise stated, all molecular weights described herein are number average molecular weights.Molecular weight can be selected based on the desired hardness of final tow or filter rod.Although larger molecular weight causes increased hardness, larger molecular weight also increases viscosity.Cellulose ester can be provided in powder or flake form.

[0037] In some aspects, blends of cellulose ester flakes or powders of different molecular weights can be used. Therefore, blends of high molecular weight cellulose esters (e.g., cellulose esters with a molecular weight higher than 60,000amu) can be blended with low molecular weight cellulose esters (e.g., cellulose esters with a molecular weight lower than 60,000amu). The ratio of high molecular weight cellulose esters to low molecular weight cellulose esters can vary, but generally can be in the range of from 1:10 to 10:1; for example, from 1:5 to 5:1 or from 1:3 to 3:1. Blends of different cellulose esters can also be used and can include two, three, four or more different cellulose esters of different ratios. In some aspects, a cellulose ester can exist in the majority, while other cellulose esters exist in lesser amounts.

[0038] Cellulose acetate fibers, tow and tow packages

[0039] There are many methods for forming fibers from cellulose acetate, which can be used to form cellulose acetate fibers of the present disclosure. In some embodiments, in order to form fibers from cellulose esters, a spinning solution is formed by dissolving the cellulose ester in a solvent to form a spinning solution solution. The spinning solution solution is typically a high viscosity solution. The solvent of the spinning solution solution can be selected from the group consisting of: water, acetone, methyl ethyl ketone, methylene chloride, dioxane, dimethylformamide, methanol, ethanol, glacial acetic acid, supercritical carbon dioxide, any suitable solvent capable of dissolving the above-mentioned polymers, and combinations thereof. In some aspects, the solvent is acetone or a combination of acetone and up to 5wt.% water. Pigments can also be added to the spinning solution. The spinning solution can contain, for example, from 10 to 40wt.% of cellulose acetate and from 60 to 90wt.% of solvent. Pigment, when added, can be with from 0.1 to 5wt.%, for example, from 0.1 to 4wt.%, from 0.1 to 3wt.%, from 0.1 to 2wt.%, from 0.5 to 5wt.%, from 0.5 to 4wt.%, from 0.5 to 3wt.%, from 0.5 to 2wt.%, from 1 to 5wt.%, from 1 to 4wt.%, from 1 to 3wt.% or from 1 to 2wt.% exist.Then, before spinning to form fiber, spinning solution is filtered and degassed.Spinning solution can be spun in a spinning machine comprising one or more chambers, and each chamber comprises a spinneret.Spinneret comprises the hole that affects the speed that solvent evaporates from fiber.

[0040] The pigment added to the spinning solution is not particularly limited, and any conventional pigment may be used. Examples of common, suitable pigments include calcium carbonate, diatomaceous earth, magnesium oxide, zinc oxide, and barium sulfate.

[0041] Generally speaking, the production of tow band packages may involve spinning fibers from a spinning solution, forming tow bands from the fibers, crimping the tow bands, and packaging the crimped tow bands. In the production, optional steps may include, but are not limited to, heating the fibers after spinning, applying a finish or additive to the fibers and / or tow bands before crimping, and conditioning the crimped tow bands. The parameters of at least these steps are important for producing the desired package.

[0042] It should be noted that the size and shape of the bag can vary according to the needs of further processing. In some embodiments, the bag can have dimensions ranging from 30 inches (76 cm) to 60 inches (152 cm) in height, 46 inches (117 cm) to 56 inches (142 cm) in length, and 35 inches (89 cm) to 45 inches (114 cm) in width. In some embodiments, the weight of the bag can range from 900 pounds (408 kg) to 2100 pounds (953 kg). In some embodiments, the bag can have a density greater than 300 kg / m3 (18.8 lb / ft3).

[0043] fiber

[0044] The structure of the cellulose acetate fiber for the present disclosure is not particularly limited, and various known fiber structures can be used. For example, the filament band can utilize a fiber with a wide range of single filament denier (dpf). In certain embodiments, the filament band has from 1 to 30 dpf, for example, from 2 to 28 dpf, from 3 to 25 dpf, from 4 to 22 dpf, from 5 to 30 dpf, from 5 to 28 dpf, from 5 to 25 dpf, from 5 to 22 dpf, from 10 to 30 dpf, from 10 to 28 dpf, from 10 to 25 dpf, from 10 to 22 dpf, from 15 to 30 dpf, from 15 to 28 dpf, from 15 to 25 dpf, from 15 to 22 dpf, from 20 to 30 dpf, from 20 to 28 dpf, from 20 to 25 dpf, or from 20 to 22 dpf.

[0045] Fibers for use in the present disclosure may have any suitable cross-sectional shape, including, but not limited to, circular, generally circular, crenulated, oval, generally oval, polygonal, generally polygonal, dog-bone, "Y", "X", "K", "C", multi-lobal, and any mixture thereof. As used herein, the term "multi-lobal" refers to a cross-sectional shape having a point (not necessarily at the center of the cross-section) from which at least two lobes extend (not necessarily evenly spaced or evenly sized).

[0046] As described above, the fiber for the present disclosure can be produced by any method known to those skilled in the art. As described, in some embodiments, the fiber can be produced by spinning the spinning solution through a spinneret. As used herein, the term "spinning solution" refers to a cellulose acetate solution and / or suspension from which the fiber is produced. In some embodiments, the spinning solution may include cellulose acetate and a solvent. In some embodiments, the spinning solution used in conjunction with the present disclosure may include cellulose acetate, a solvent, and an additive. In some embodiments, the concentration range of cellulose acetate in the spinning solution may be from 10 to 40wt.% (e.g., from 20 to 30wt.%, from 25 to 40wt.%, from 25 to 30wt.%), and the concentration of the solvent may be from 60 to 90wt.% (e.g., 60 to 80wt.%, 70 to 80wt.%, 80 to 90wt.%). In some embodiments, the spinning dope may be heated to a temperature ranging from 40°C to 100°C (eg, from 45°C to 95°C, from 50°C to 90°C, from 55°C to 85°C, from 60°C to 80°C).

[0047] Suitable solvents may include, but are not limited to, water, acetone, methyl ethyl ketone, methylene chloride, dioxane, dimethylformamide, methanol, ethanol, glacial acetic acid, supercritical CO2, any suitable solvent capable of dissolving the above-mentioned polymer, or any combination thereof. As a non-limiting example, the solvent for cellulose acetate may be an acetone / methanol mixture. In certain embodiments, in order to produce the very high dpf value of the present disclosure, the solvent level increased compared to the amount of typical dpf values ​​(e.g., 2 to 8 dpf) may be used. For example, in certain embodiments, in order to produce the tow of very high dpf, the amount of solvent may be high from 5 to 30wt.% when compared to the amount of solvent of typical dpf tow. In some cases, the additional amount of solvent may bring challenges to the processing of fiber.

[0048] Some embodiments of the present disclosure may involve treating fibers to achieve surface functionality on the fibers. In some embodiments, the fibers may include surface functionality, including but not limited to biodegradable sites (e.g., defect sites that increase surface area to improve biodegradability), chemical treatments (e.g., carboxylic acid groups for subsequent functionalization), active particle binding sites (e.g., sulfide sites for binding gold particles or chelating groups for binding iron oxide particles), sulfur moieties, or any combination thereof. One skilled in the art will appreciate the various methods and mechanisms for achieving surface functionality. Some embodiments may involve impregnation, spraying, ionization, functionalization, acidification, hydrolysis, exposure to plasma, exposure to ionized gases, or any combination thereof to achieve surface functionality. Suitable chemicals for imparting surface functionality may be any chemical or collection of chemicals that can react with cellulose acetate, including but not limited to acids (e.g., sulfuric acid, nitric acid, acetic acid, hydrofluoric acid, hydrochloric acid, etc.), reducing agents (e.g., LiAlH4, NaBH4, H2 / Pt, etc.), Grignard reagents (e.g., CH3MgBr, etc.), transesterification agents, amines (e.g., R-NH3 such as CH3NH3), or any combination thereof. Exposure to plasma and / or ionized gas may react with the surface, create defects in the surface, or any combination thereof. The defects may increase the surface area of ​​the fiber, which may result in higher loading and / or higher filtration efficacy in the final filter product.

[0049] Some embodiments of the present disclosure may involve applying a finish to the fibers. Suitable finishes may include, but are not limited to, at least one of: oil (e.g., mineral oil or a liquid petroleum derivative), water, an additive, or any combination thereof. Examples of suitable mineral oils may include, but are not limited to, colorless, transparent (i.e., clear) mineral oils having a viscosity of 80-95 SUS (Sabolt Universal Seconds) measured at 38° C. (100° F.). Examples of suitable emulsifiers may include, but are not limited to, sorbitan monolaurate, such as 20 (available from Croda, Wilmington, Del.), poly(ethylene oxide) sorbitan monolaurate, e.g. 20 (available from Croda Corporation, Wilmington, Delaware). The water may be demineralized water, deionized water, or other suitable filtered and treated water. The lubricant or finish may be applied by spraying or wiping. Generally, the lubricant or finish is added to the fibers before the fibers are formed into tow.

[0050] In some embodiments of the present disclosure, the finish may be applied as a neat finish or as a finish emulsion in water. As used herein, the term "neat finish" refers to a finish formulation without the addition of excess water. It should be noted that the finish formulation may include water. In some embodiments, the finish may be applied neat, followed by a separate application of water.

[0051] In some embodiments of the present disclosure, the finish emulsion may contain less than 98%, less than 95%, less than 92%, or less than 85% water. In some embodiments, it may be desirable to obtain fibers with a lower weight percentage of moisture (e.g., 5% to 25% w / w of the tow band) in subsequent steps where water is a contributor. The water content of the finish emulsion may be at least one parameter that can help achieve the stated weight percentage of moisture in the fiber. Thus, in some embodiments, the finish emulsion may contain less than 92% water, less than 85% water, or less than 75% water.

[0052] Tow

[0053] The present disclosure preferably includes forming a tow band from a plurality of fibers. In some embodiments, the tow band is from 10,000 to 100,000 total denier, for example, from 15,000 to 100,000, from 20,000 to 100,000, from 25,000 to 100,000, from 30,000 to 100,000, from 10,000 to 90,000, from 15,000 to 90,000, from 20,000 to 90,000, from 25,000 to 90,000, from 30,000 to 90,000, from 10,000 to 90,000, from 15,000 to 90,000, from 20,000 to 90,000, from 25,000 to 90,000, from 30 From 10,000 to 90,000, from 10,000 to 80,000, from 15,000 to 80,000, from 20,000 to 80,000, from 25,000 to 80,000, from 30,000 to 80,000, from 10,000 to 70,000, from 15,000 to 70,000, from 20,000 to 70,000, from 25,000 to 70,000, from 30,000 to 70,000, from 10,000 to 60,000, from 15,000 to 60,000, from 20,000 to 60,000, from 25,000 to 60,000, or from 30,000 to 60,000. As for the upper limit, the tow band can be less than 100,000 total denier, for example, less than 90,000, less than 80,000, less than 70,000, or less than 60,000. As for the lower limit, the tow band can be greater than 10,000 total denier, for example, greater than 15,000, greater than 20,000, greater than 25,000, or greater than 30,000.

[0054] In some embodiments, the tow may have a breaking strength between 3.5kg and 25kg, for example, from 3.5kg to 22.5kg, from 3.5kg to 20kg, from 3.5kg to 17.5kg, from 3.5kg to 15kg, from 4kg to 25kg, from 4kg to 22.5kg, from 4kg to 20kg, from 4kg to 17.5kg, from 4kg to 15kg, from 4.5kg to 25kg, from 4.5kg to 22.5kg, from 4.5kg to 20kg, from 4.5kg to 17.5kg, from 4.5kg to 15kg, from 5kg to 25kg, from 5kg to 22.5kg, from 5kg to 20kg, from 5kg to 17.5kg, or from 5kg to 15kg. In terms of upper limit, the tow can have a breaking strength of less than 25 kg, for example, less than 22.5 kg, less than 20 kg, less than 17.5 kg, or less than 15 kg. In terms of lower limit, the tow can have a breaking strength greater than 3.5 kg, for example, greater than 4 kg, greater than 4.5 kg, or greater than 5 kg.

[0055] In some embodiments of the present disclosure, the tow band may include more than one type of fiber. In some embodiments, the more than one type of fiber may vary based on dpf, cross-sectional shape, composition, treatment prior to forming the tow band, or any combination thereof. Examples of suitable additional fibers may include, but are not limited to, carbon fibers, activated carbon fibers, natural fibers, synthetic fibers, or any combination thereof.

[0056] Some embodiments of the present disclosure may include crimping the tow band to form a crimped tow band. The crimping of the tow band may involve using any suitable crimping technique known to those skilled in the art. These techniques may include various devices, including but not limited to stuffer boxes or gears. Non-limiting examples of crimping devices and their working mechanisms can be found in U.S. Patent Nos. 7,610,852 and 7,585,441, the entire contents and disclosures of which are incorporated herein by reference. Suitable stuffer box crimpers may have smooth crimper nip rollers, threaded or grooved crimper nip rollers, textured crimper nip rollers, upper platens, lower platens, or any combination thereof.

[0057] The configuration of the curl can play a role in the processability of the final package. Examples of curl configurations may include, but are not limited to, transverse, vertical, some degree between transverse and vertical, random, or any combination thereof. As used herein, the term "transverse" when describing the curl orientation refers to curling or fiber bending within the plane of the tow band. As used herein, the term "vertical" when describing the curl orientation refers to curling that protrudes beyond the plane of the tow band and is perpendicular to the plane of the tow band. It should be noted that the terms transverse and vertical refer to the typical overall curl orientation and may have a deviation of + / - 30 degrees from the described configuration.

[0058] In some embodiments of the present disclosure, a crimped tow band may include fibers having a first crimped configuration and fibers having a second crimped configuration.

[0059] In some embodiments of the present disclosure, the curled tow band may include fibers having at least a vertical curl configuration near the edges and fibers having at least a transverse curl configuration near the center. In some embodiments, the curled tow band may include fibers having a vertical curl configuration near the edges and fibers having a transverse curl configuration near the center.

[0060] The crimped configuration can be important for the processability of the final package in subsequent processing steps, for example, a transverse crimped configuration can provide better fiber adhesion than a vertical crimped configuration unless additional steps are taken to improve adhesion. Methods for crimping a tow band having a substantially transverse crimped configuration are disclosed, for example, in U.S. Patent Nos. 2013 / 0115452 and 2015 / 0128964, each of which is incorporated herein in its entirety.

[0061] In some embodiments of the present disclosure, fibers can adhere to each other to provide better processability of final bag. Although adhesion additives can be used in combination with any curling structure, it may be advantageous to use adhesion additives together with vertical curling structure. In certain embodiments, adhesion may involve adhesion additives on and / or in the fiber. Examples of such adhesion additives may include but are not limited to binders, adhesives, resins, tackifiers or any combination thereof. It should be noted that any additive described herein or other additives that can adhere two fibers together may be used, and these additives may include but are not limited to active particles, active compounds, ionic resins, zeolites, nanoparticles, ceramic particles, softeners, plasticizers, pigments, dyes, flavorings, fragrances, controlled release vesicles, surface modifiers, lubricants, emulsifiers, vitamins, peroxides, biocides, fungicides, antimicrobials, antistatic agents, flame retardants, defoamers, degradation agents, conductive modifiers, stabilizers or any combination thereof. Some embodiments of the present disclosure may involve adding a binder additive to fibers (in, on, or both) by incorporating the binder additive into a spinning solution, incorporating the binder additive into a finish, applying the binder additive to the fibers (before, after, and / or during formation of a tow band), applying the binder additive to a tow band (before, after, and / or during crimping), or any combination thereof.

[0062] Binder additives may be included in and / or on the fibers in a concentration sufficient to adhere the fibers together at multiple contact points to provide better processability of the final package. The concentration of the binder additive to be used may depend on the type of binder additive and the adhesion strength provided by the binder additive. In some embodiments, the concentration of the binder additive may range from a lower limit of 0.01%, 0.05%, 0.1%, or 0.25% to an upper limit of 5%, 2.5%, 1%, or 0.5% (by weight of the tow band in the final package). It should be noted that for additives used for more than just adhesion, the concentration in the tow band in the final package may be higher, such as 25% or less.

[0063] In addition, some embodiments of the present disclosure may involve heating the fibers before, after, and / or during crimping. While the heating may be used in conjunction with any crimping configuration, it may be advantageous to use the heating with a vertical crimping configuration. The heating may involve exposing the fibers of the tow band to steam, an atomized compound (e.g., a plasticizer), a liquid, a heating fluid, a direct heat source, an indirect heat source, a radiation source that generates heat for additives (e.g., nanoparticles) in the fibers, or any combination thereof.

[0064] Some embodiments of the present disclosure may include conditioning the curled tow band. Conditioning may be used to achieve a curled tow band having a residual acetone content of 0.5% or less w / w of the curled tow band. Conditioning may be used to achieve a curled tow band having a residual water content of 8% or less w / w of the curled tow band. Conditioning may involve exposing the fibers of the curled tow band to steam, an atomized compound (e.g., a plasticizer), a liquid, a heated fluid, a direct heat source, an indirect heat source, a radiation source that generates heat to an additive (e.g., nanoparticles) in the fibers, or any combination thereof.

[0065] UCE is the amount of work required to uncrimp the fiber. As reported below, UCE was sampled before baling (i.e., after drying and before baling). As used herein, UCE is measured as follows: Using a preheated (20 minutes prior to routine calibration) Instron tensile tester (Model 1130, crosshead gear - gear numbers R1940-1 and R940-2, Instron Series IX - Version 6 data acquisition and analysis software, Instron 50 Kg maximum capacity load cell, Instron top roller assembly, 1" x 4" x 1 / 8" thick high grade Buna-N 70 Shore A Durometer rubber grip face), a preconditioned tow sample (preconditioned for 24 hours at 22°C ± 2°C and 60% ± 2% relative humidity) of approximately 76 cm in length is looped around the center of the top roller and evenly distributed, pre-stretched by gently pulling to 100 g ± 2 g (according to the readout display), and each end of the sample is clamped in the lower grip (at the highest available pressure, but not exceeding the manufacturer's recommendation) to achieve a 50 cm gauge length (the gauge length is measured from the top of the rubber grip), and then tested at a crosshead speed of 30 cm / min until fracture. Repeat this test until three acceptable tests are obtained, and report the average of the three data points for these tests. Energy (E) limit at 0.220kg and 10.0kg. Displacement (D) has a preset point of 10.0kg. UCE is calculated by the following formula: UCE (gcm / cm) = (E*1000) / ((D*2) + 500). Breaking strength can be calculated using the same test and the following equation BS = L (where L is the load at maximum load (kg)). In certain embodiments of the present disclosure, the UCE value (in gcm / cm) can range from 190 to 400, such as 200 to 300, such as 290. In certain embodiments of the present disclosure, the breaking strength can range from 3.5kg to 25kg, such as 4kg to 20kg, 4.5kg to 15kg, or 5kg to 12kg.

[0066] Once formed, the pellets described herein can be added to the cellulose acetate tow and can be added during the manufacture of the stick. For example, the pellets can be added to the tow using a tablet inserter, such as a tablet inserter used to add flavor ingredients to existing products.

[0067] Cigarette Filters

[0068] Degradable cigarette filters generally include a filter element (or filter rod) made of expanded cellulose acetate tow, a filter rod wrapping paper surrounding the filter element, and a pill dispersed in the tow. The pill can be added to the filter element during the manufacture of the cigarette filter. The pill can be a single pill or a plurality of pills. In some aspects, the cigarette filter can be a special item that includes cellulose acetate in a form other than the expanded tow. The disclosure provided herein will also be applicable to such filters, and the pill will be similarly dispersed in the cellulose acetate of such filters.

[0069] The weight, size and amount of the pills included in the tow can be determined by the desired deacetylation rate of the cellulose acetate in the tow, and can also be selected based on the filter type, such as fine, superfine and oversize. Thus, the size of the pills can be selected based on the quality of the filter size. The weight ratio of pills to tow can be from 1:50 to 1:1, such as from 1:25 to 1:2, or from 1:10 to 1:2.

[0070] Cellulose ester products

[0071] The composition of the present invention can be formed into fibers, films and other widely used molded products by conversion processes such as extrusion, thermoforming, blow molding, 3D printing and injection molding. Exemplary products include disposable tableware, food supply items (plates, bowls, cups), films, sporting goods, etc. According to application, the products of the present disclosure can also include one or more additives selected from the group consisting of: active particles, antioxidants, active compounds, ion exchange resins, zeolites, nanoparticles, ceramic particles, abrasive particles, fillers, absorbent particles, softeners, pigments, dyes, flavorings, aromatics, controlled release vesicles, binders, adhesives, tackifiers, surface modifiers, lubricants, emulsifiers, vitamins, peroxides, biocides, fungicides, antimicrobials, deodorants, antistatic agents, defoamers, degradation agents, conductive modifiers and stabilizers.

[0072] Active particles used in conjunction with the present disclosure can be used to actively reduce components in a fluid stream by absorption or reaction. Suitable active particles for use in conjunction with the present invention may include, but are not limited to, nanoscale carbon particles, carbon nanotubes having at least one wall, carbon nanohorns, bamboo-like carbon nanostructures, fullerenes, fullerene aggregates, graphene, several layers of graphene, graphene oxide, iron oxide nanoparticles, nanoparticles, metal nanoparticles, gold nanoparticles, silver nanoparticles, metal oxide nanoparticles, aluminum oxide nanoparticles, magnetic nanoparticles, paramagnetic nanoparticles, superparamagnetic nanoparticles, gadolinium oxide nanoparticles, hematite nanoparticles, magnetite nanoparticles, gadolinium nanotubes, endohedral fullerenes, Gd@C 60, core-shell nanoparticles, onion-shaped nanoparticles, nanoshells, onion-shaped iron oxide nanoparticles, activated carbon, ion exchange resins, desiccants, silicates, molecular sieves, silica gel, activated alumina, zeolites, perlite, sepiolite, fuller's earth, magnesium silicate, metal oxides, iron oxide, activated carbon, and any combination thereof.

[0073] Antioxidants used in conjunction with the present disclosure may include phosphite antioxidants, amine antioxidants, phenolic antioxidants, and mixtures thereof. Phosphite antioxidants may include those manufactured by BASF under the trade name Trinonylphenyl phosphate, tri-tert-butylphenyl phosphite, tridecyl phosphite, triphenyl phosphite, trioctyl phosphite, alkylphenyl phosphite, tri(alkylphenyl) phosphate, dilauryl phosphite sold by TNPP are also available under the trade name 126. Amine antioxidants may include secondary aromatic amines such as diarylamines, for example diphenylamine, and modified diarylamines, for example N-phenyl-g-naphthylamine, p-isopropoxydiphenylamine, mono- and dioctyldiphenylamine, bis-diarylamines and modified bis-diarylamines, such as N,N-diphenyl-p-phenylenediamine. Phenolic antioxidants may include iododiethylenebis(3,5-di-tert-alkyl-4-hydroxyhydrocinnamate, more preferably diisocyanate sold by BASF under the trade name Thiodiethylenebis(3,5-di-tert-butyl-4-hydroxyhydrocinnamate) and tetrakis[methylene(3,5-di-tert-alkyl-4-hydroxyhydrocinnamate)]methane, more preferably sold by BASF under the trade name 1010 Tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate)]methane sold.

[0074] Suitable active particles for use in conjunction with the present disclosure may have at least one dimension that is approximately less than one nanometer, such as graphene, as large as particles having a diameter of about 5000 nanometers. The lower limit of the size of the active particles for use in conjunction with the present invention in at least one dimension may be about: 0.1 nanometer, 0.5 nanometer, 1 nanometer, 10 nanometers, 100 nanometers, 500 nanometers, 1 micron, 5 microns, 10 microns, 50 microns, 100 microns, 150 microns, 200 microns and 250 microns. The upper limit of the size of the active particles in at least one dimension may be about: 5000 microns, 2000 microns, 1000 microns, 900 microns, 700 microns, 500 microns, 400 microns, 300 microns, 250 microns, 200 microns, 150 microns, 100 microns, 50 microns, 10 microns and 500 nanometers. Any combination of the above lower and upper limits may be suitable for use in conjunction with the present invention, wherein the selected maximum size is greater than the selected minimum size. In some embodiments, the active particles used in conjunction with the present invention may be a mixture of particle sizes ranging from the lower and upper limits above. In some embodiments of the present invention, the size of the active particles may be multimodal.

[0075] Suitable ion exchange resins for use in conjunction with the present disclosure may include, but are not limited to, polymers having backbones such as styrene-divinylbenzene (DVB) copolymers, acrylates, methacrylates, phenol formaldehyde condensates, and epichlorohydrinamine condensates; multiple charged functional groups attached to the polymer backbone; or any combination thereof.

[0076] As used herein, the term "superabsorbent material" refers to a material, such as a polymer, that is capable of absorbing at least three times its weight in fluid. Suitable superabsorbent materials for use in conjunction with the present invention may include, but are not limited to, sodium polyacrylate, starch graft copolymers of polyacrylonitrile, polyvinyl alcohol copolymers, cross-linked poly(ethylene oxide), polyacrylamide copolymers, ethylene maleic anhydride copolymers, cross-linked carboxymethyl cellulose, and the like, or any combination thereof. As a non-limiting example, superabsorbent materials incorporated into nonwovens may be used in chemical spill wipes and kits.

[0077] Zeolites used in conjunction with the present disclosure may include crystalline aluminosilicates having pores, such as channels or cavities, of uniform molecular size. Zeolites may include natural and synthetic materials. Suitable zeolites may include, but are not limited to, zeolite BETA (Na7(Al7Si 57 O 128 ) tetragonal), zeolite ZSM-5 (Na n (Al n Si 96-n O 192)16H2O, wherein n<27), zeolite A, zeolite X, zeolite Y, zeolite KG, zeolite ZK-5, zeolite ZK-4, mesoporous silicate, SBA-15, MCM-41, MCM48 modified by 3-aminopropylsilyl, aluminophosphate, mesoporous aluminosilicate, other related porous materials (e.g., such as mixed oxide gel), or any combination thereof.

[0078] Suitable nanoparticles for use in conjunction with the present disclosure may include, but are not limited to, nanoscale carbon particles such as carbon nanotubes with any number of walls, carbon nanohorns, bamboo-like carbon nanostructures, fullerenes and fullerene aggregates, and graphene (including several layers of graphene and graphene oxide); metal nanoparticles such as gold and silver; metal oxide nanoparticles such as aluminum oxide, silicon dioxide, and titanium dioxide; magnetic, paramagnetic, and superparamagnetic nanoparticles such as gadolinium oxide, iron oxides of various crystal structures such as hematite and magnetite, Fe3O4 of about 12 nm, gadolinium nanotubes, and endohedral fullerenes such as Gd@C 60 ; and core-shell and onion-shaped nanoparticles such as gold and silver nanoshells, onion-shaped iron oxide, and other nanoparticles or microparticles having shells of any of the materials described; and any combination of the above. It should be noted that nanoparticles may include nanorods, nanospheres, nanometers, nanowires, nanostars (such as nanotripods and nanotetrapods), hollow nanostructures, hybrid nanostructures connected as one by two or more nanoparticles, and non-nanoparticles with nanocoatings or nanothick walls. It should be further noted that the nanoparticles used in conjunction with the present invention may include functionalized derivatives of nanoparticles, including but not limited to nanoparticles that have been functionalized covalently and / or non-covalently (e.g., π-stacking, physical adsorption, ionic association, van der Waals association, etc.). Suitable functional groups may include, but are not limited to, moieties comprising amines (1°, 2°, or 3°), amides, carboxylic acids, aldehydes, ketones, ethers, esters, peroxides, silyl groups, organosilanes, hydrocarbons, aromatic hydrocarbons, and any combination thereof; polymers; chelating agents such as ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, nitrilotriacetic acid, and structures comprising pyrrole rings; and any combination thereof.

[0079] Suitable ceramic particles for use in conjunction with the present invention may include, but are not limited to, oxides (e.g., silicon dioxide, titanium dioxide, aluminum oxide, beryllium oxide, ceria, and zirconium oxide), non-oxides (e.g., carbides, borides, nitrides, and silicides), composites thereof, or any combination thereof. The ceramic particles may be crystalline, amorphous, or semi-crystalline.

[0080] Suitable softeners for use in conjunction with the present invention may include, but are not limited to, water, triacetin, triethyl citrate, dimethoxy-ethyl phthalate, dimethyl phthalate, diethyl phthalate, glycolic acid methylphthaloylethyl ester, o-phenylphenyl-(bis)phenyl phosphate, 1,4-butanediol diacetate, diacetate, dipropionate of triethylene glycol, dibutyrate of triethylene glycol, dimethoxyethyl phthalate, triethyl citrate, triacetin, and the like, any derivatives thereof, and any combination thereof.

[0081] As used herein, pigment refers to compounds and / or particles that impart color and are incorporated into the entire filament. Suitable pigments used in conjunction with the present invention may include but are not limited to titanium dioxide, silicon dioxide, carbon black, tartrazine, E102, phthalocyanine blue, phthalocyanine green, quinacridone, perylene tetracarboxylic acid diimide, dioxazine, pyrene ketone disazo pigment, anthraquinone pigment, carbon black, metal powder, iron oxide, ultramarine, calcium carbonate, kaolin, aluminum hydroxide, barium sulfate, zinc oxide, aluminum oxide, caramel, fruit or vegetable or spice coloring agent (such as beet powder, beta-carotene, turmeric, paprika) or any combination thereof. In some aspects, cellulose acetate tow, cigarette filter and cellulose ester products are substantially free of or free of titanium dioxide, particularly serving as the titanium dioxide of the primary reagent for degradation.

[0082] As used herein, dye refers to compounds and / or particles that impart color and provide surface treatment to filaments. Suitable dyes for use in conjunction with the present invention may include, but are not limited to, liquid and / or granular forms. Dyes (cationic dyes, available from Clariant Services) (e.g., Bright yellow K-6G liquid, Yellow K-4GL liquid, Yellow K-GL liquid, Orange K-3GL liquid, Scarlet K-2GL liquid, Red K-3BN liquid, Blue K-5R liquid, Blue K-RL liquid, Blue-green K-RL liquid / granules, Brown K-BL liquid), Dyes (auxochromes, available from BASF) (eg, Yellow 3GL, Fastusol C Blue 74L).

[0083] Suitable flavoring agents used in combination with the present invention may include but are not limited to organic materials (or natural flavor particles), carriers of natural flavors, carriers of artificial flavors, and any combination thereof.Organic materials (or natural flavor particles) include but are not limited to tobacco, cloves (e.g., clove powder and cloves), cocoa, etc.Natural and artificial flavors may include but are not limited to menthol, cloves, cherries, chocolate, oranges, mint, mangoes, vanilla, cinnamon, tobacco, etc.Such flavors may be provided by menthol, anethole (licorice), anisole, limonene (citrus), eugenol (cloves), etc., or any combination thereof.In certain embodiments, more than one flavoring agent may be used, including any combination of flavoring agents provided herein.

[0084] Suitable fragrances for use in conjunction with the present disclosure may include, but are not limited to, methyl formate, methyl acetate, methyl butyrate, ethyl acetate, ethyl butyrate, isoamyl acetate, amyl butyrate, amyl valerate, octyl acetate, myrcene, geraniol, nerol, citral, citronellal, citronellol, linalool, nerolidol, limonene, camphor, terpineol, α-ionone, thujone, benzaldehyde, eugenol, cinnamaldehyde, ethyl maltol, vanilla, anethole, anethole, estragole, thymol, furanone, methanol, or any combination thereof.

[0085] Suitable binders used in combination with the present disclosure may include but are not limited to polyolefins, polyesters, polyamides (or nylons), polyacrylates, polystyrenes, polyethylene compounds, polytetrafluoroethylene (PTFE), polyetheretherketone (PEEK), any copolymers thereof, any derivatives thereof, and any combinations thereof. Non-fibrous plasticized cellulose derivatives may also be suitable for use as binder particles in the present invention. Examples of suitable polyolefins may include but are not limited to polyethylene, polypropylene, polybutene, polymethylpentene, etc., any copolymers thereof, any derivatives thereof, and any combinations thereof. Examples of suitable polyethylene may include but are not limited to ultra-high molecular weight polyethylene, extremely high molecular weight polyethylene, high molecular weight polyethylene, low density polyethylene, linear low density polyethylene, high density polyethylene, etc., any copolymers thereof, any derivatives thereof, and any combinations thereof. Examples of suitable polyesters may include but are not limited to polyethylene terephthalate, polybutylene terephthalate, polycyclohexylene dimethylene terephthalate, polytrimethylene terephthalate, etc., any copolymers thereof, any derivatives thereof, and any combinations thereof. The example of suitable polyacrylate may include but is not limited to polymethyl methacrylate, etc., any copolymer thereof, any derivative thereof, and any combination thereof. The example of suitable polystyrene may include but is not limited to polystyrene, acrylonitrile-butadiene-styrene, styrene-acrylonitrile, styrene-butadiene, styrene-maleic anhydride, etc., any copolymer thereof, any derivative thereof, and any combination thereof. The example of suitable polyethylene compound may include but is not limited to ethylene vinyl acetate, ethylene vinyl alcohol, polyvinyl chloride, etc., any copolymer thereof, any derivative thereof, and any combination thereof. The example of suitable cellulosic plastic may include but is not limited to cellulose acetate, cellulose acetate butyrate, plasticized cellulose, cellulose propionate, ethyl cellulose, etc., any copolymer thereof, any derivative thereof, and any combination thereof. In some embodiments, the binder particles may include any copolymer, any derivative, or any combination of the binders listed above. In addition, the binder particles may be impregnated with and / or coated with any combination of additives disclosed herein.

[0086] Suitable viscosity increasing agents for use in conjunction with the present disclosure may include, but are not limited to, methylcellulose, ethylcellulose, hydroxyethylcellulose, carboxymethylcellulose, carboxyethylcellulose, water-soluble cellulose acetate, amides, diamines, polyesters, polycarbonates, silyl-modified polyamide compounds, polyurethanes, polyurethanes, natural resins, shellac, acrylic acid polymers, 2-ethylhexyl acrylate, acrylate polymers, acrylic acid derivative polymers, acrylic acid homopolymers, acrylate homopolymers, poly(methyl acrylate), poly(butyl acrylate), poly(2-ethylhexyl acrylate), acrylate copolymers, methacrylic acid derivative polymers, methacrylic acid homopolymers, methacrylate homopolymers, poly( methyl methacrylate), poly(butyl methacrylate), poly(2-ethylhexyl methacrylate), acrylamido-methyl-propane sulfonate polymer, acrylamido-methyl-propane sulfonate derivative polymer, acrylamido-methyl-propane sulfonate copolymer, acrylic acid / acrylamido-methyl-propane sulfonate copolymer, benzyl coconut oil di-(hydroxyethyl) quaternary amine, p-tert-amylphenol condensed with formaldehyde, dialkylaminoalkyl (meth)acrylate, acrylic acid amide, N-(dialkylaminoalkyl)acrylamide, methacrylamide, hydroxyalkyl (meth)acrylate, methacrylic acid, acrylic acid, hydroxyethyl acrylate, etc., any derivatives thereof, or any combination thereof.

[0087] Suitable lubricants for use in conjunction with the present disclosure may include, but are not limited to, ethoxylated fatty acids (e.g., the reaction product of ethylene oxide and nonanoic acid to form poly(ethylene glycol) ("PEG") monononanoate; the reaction product of ethylene oxide and coconut fatty acid to form PEG monolaurate), and the like, or any combination thereof. Lubricants may also be selected from non-water soluble materials such as synthetic hydrocarbon oils, alkyl esters (e.g., tridecyl stearate, which is the reaction product of tridecanol and stearic acid), polyol esters (e.g., trimethylolpropane trinonanoate and pentaerythritol tetranonanoate), and the like, or any combination thereof.

[0088] Suitable emulsifiers for use in conjunction with the present disclosure may include, but are not limited to, sorbitan monolaurate, e.g. 20 (available from Uniqema, Wilmington, Del.), or poly(ethylene oxide)sorbitan monolaurate, e.g. 20 (available from Liquichem, Inc., Wilmington, Delaware).

[0089] Suitable vitamins for use in conjunction with the present disclosure may include, but are not limited to, vitamin B compounds (including B1 compounds, B2 compounds, B3 compounds such as niacinamide, niacin, tocopherol nicotinate, C1-C 18Nicotinic acid esters and nicotinyl alcohols; B5 compounds such as panthenol or "pro-B5", pantothenic acid, pantothenoyl; B6 compounds such as pyroxidine, pyridoxal, pyridoxamine; carnitine, thiamine, riboflavin); vitamin A compounds, and all natural and / or synthetic analogs of vitamin A, including retinoids, retinol, retinyl acetate, retinyl palmitate, retinoic acid, retinal, retinyl propionate, carotenoids (provitamin A), and other biologically active substances that have vitamin A compounds; vitamin D compounds; vitamin K compounds; vitamin E compounds, or tocopherols, including tocopherol sorbate, tocopherol acetate, other esters of tocopherol and tocopherol compounds; vitamin C compounds, including ascorbate, ascorbyl esters of fatty acids and ascorbic acid derivatives, for example, ascorbyl phosphates such as magnesium ascorbyl phosphate and sodium ascorbyl phosphate, ascorbyl glucoside, and ascorbyl sorbate; and vitamin F compounds, such as saturated and / or unsaturated fatty acids; or any combination thereof.

[0090] Suitable antimicrobial agents for use in conjunction with the present disclosure may include, but are not limited to, antimicrobial metal ions, chlorhexidine, chlorhexidine salts, triclosan, polymyxins, tetracyclines, aminoglycosides (e.g., gentamicin), rifampicin, bacitracin, erythromycin, neomycin, chloramphenicol, miconazole, quinolones, penicillins, nonoxynol 9, fusidic acid, cephalosporins, mupirocin, metronidazole, secropin), antimicrobial peptides, bacteriocins, defensins, nitrofuracil, mafenide, acyclovir, vancomycin, clindamycin, lincomycin, sulfonamides, norfloxacin, pefloxacin, nalidizic acid, oxalic acid, enoxacin acid, ciprofloxacin, polyhexamethylene biguanide (PHMB), PHMB derivatives (e.g., biodegradable biguanides such as polyethylene hexamethylene biguanide (PEHMB)), chlorhexidine gluconate, chlorhexidine hydrochloride, ethylenediaminetetraacetic acid (EDTA), EDTA derivatives (e.g., disodium EDTA or tetrasodium EDTA), etc., and any combination thereof.

[0091] Antistatic agents (antistatic agents) used in conjunction with the present disclosure may include any suitable anionic, cationic, amphoteric or nonionic antistatic agents. Anionic antistatic agents may generally include, but are not limited to, alkali sulfates, alkali phosphates, phosphate esters of alcohols, phosphate esters of ethoxylated alcohols, or any combination thereof. Examples may include, but are not limited to, alkali-neutralized phosphate esters (e.g., 5559 or 5576, available from Henkel Corporation, Mauldin, SC). Cationic antistatic agents generally can include, but are not limited to, quaternary ammonium salts and imidazolines having a positive charge. Examples of nonionics include poly(oxyalkylene) derivatives, for example, ethoxylated fatty acids such as 2650 (ethoxylated fatty acids, available from Henkel Corporation, Mauldin, South Carolina), ethoxylated fatty alcohols such as 5964 (ethoxylated lauryl alcohol, available from Henkel Corporation, Mauldin, South Carolina), ethoxylated fatty amines such as 6606 (ethoxylated tallow amine, available from Henkel Corp., Mauldin, SC), alkanolamides such as 6545 (diethanolamine oleate, available from Henkel Corporation, Mauldin, South Carolina), or any combination thereof. Anionic and cationic materials tend to be more effective antistatic agents.

[0092] pill

[0093] In order to help the degradation of cellulose acetate, especially cellulose acetate tow, a pellet containing an alkaline material, an enzyme material, or a combination thereof is dispersed in the tow or cellulose ester product. Compared with other methods that include degradation aids in the tow or product, there are several advantages in dispersing this pellet in the tow or product. For example, if the alkaline material or enzyme material is simply added to the tow during the manufacture of the tow and dispersed in the tow as particles in the fiber, the availability of the material will be limited and the material will not help the degradation of the cellulose acetate tow. This method may also be diffusion-limited. For some specific alkaline materials, such as calcium oxide or calcium hydroxide, including the material as particles in the tow will cause the tow to degrade soon after the tow is manufactured because the environmental moisture will activate the degradation. On the contrary, by including the pellet, the environmental moisture will not activate the degradation prematurely. The pellet is also configured to allow the material to be available when exposed to water exceeding the ambient level, and the degradation will not be diffusion-limited.

[0094] Another advantage of including an alkaline material or an enzyme material is the time required to hydrolyze the acetate moiety compared to an acidic material. Although acids can hydrolyze the acetate moiety, they are slower than alkaline materials or enzyme materials. This relatively slow hydrolysis can be problematic when the cigarette filter is discarded in the environment. For example, if the filter is discarded in a puddle, or if a heavy rainstorm hits, the acidic material may be washed out of the cellulose acetate tow, and thus no acidic material is left to catalyze the degradation of the cellulose acetate. In contrast, alkaline materials quickly hydrolyze cellulose acetate when immersed in water, allowing deacetylation to occur before the alkaline material is washed out of the tow. The same applies to cellulose ester products, such as films or even disposable tableware. The availability of degradation aids is key.

[0095] By including an alkaline material or an enzyme material, particularly a material capable of deacetylating at least 10% of the cellulose acetate tow or cellulose ester in the article in 20 days or less when exposed to water, the likelihood that the alkaline material or enzyme material will be washed out before its catalyst is degraded is greatly reduced. As used herein, "when exposed to water" means that the tow containing the pellets is completely immersed in water at room temperature (e.g., from 22°C to 25°C) and standard pressure.

[0096] In addition, compared with acidic materials, by comprising alkaline materials or enzyme materials, the cellulose acetate tow, cellulose ester products and any waste from them are closer to neutral than acidic materials. Not bound by theory, it is believed that this will occur because different from the acid catalyst that makes carbonyl protonate, alkaline materials are actually consumed. In some aspects, alkaline materials have an initial pH greater than 7.4, and the cellulose acetate tow has a pH less than 7.4 after being deacetylated by alkaline materials, for example, less than 7.3, less than 7.2 or less than 7.1 pH. With regard to lower limits, the cellulose acetate tow has at least 6, for example, at least 6.2, at least 6.4, at least 6.6 or at least 6.8 pH after being deacetylated by alkaline materials. In some aspects, alkaline materials have an initial pH greater than 7.6, and the tow has a pH less than 7.4 after being deacetylated by alkaline materials. In some other aspects, pH reduces at least 2 pH units. In some aspects, the pH of the cellulose acetate tow after being deacetylated is about 7.

[0097] As used herein, the term "pill" refers to a tablet or capsule, including a soft capsule, a hard capsule, a gelatin capsule, a liquid capsule, a controlled release capsule, a controlled release tablet, a caplet. Based on the size of the maximum diameter of the pill, the size range of the pill can be from 1 to 10 mm, for example, from 1 to 9 mm, from 1 to 8 mm, from 1 to 7 mm, from 1 to 5 mm, from 3 to 10 mm, or from 4 to 10 mm. The pill can be formed in any known shape. As used herein, the term "pill" is not just particles of alkaline material and / or enzyme material dispersed in a tow.

[0098] In some aspects, when the pill is a liquid capsule, the liquid capsule is crushable. The liquid capsule may have a crushing strength that allows the user to crush the liquid capsule with his or her fingers. Such capsules have been described in, for example, U.S. Patent No. 10,015,984, the entire contents and disclosures of which are incorporated by reference. The liquid capsule may contain a catalyst and may optionally contain an additional hydrolyzing agent. The liquid capsule may be spherical to allow insertion by a standard tablet inserter, but the shape is not limited to a spherical shape.

[0099] The alkaline material can include at least one of calcium carbonate, calcium oxide, calcium hydroxide, magnesium hydroxide, magnesium oxide, sodium phosphate or a combination thereof. The pH of the alkaline material can be at least greater than 7.0, such as at least 7.4, at least 7.5, at least 7.6, at least 7.7, at least 7.8, at least 7.9 or at least 8.0. In some aspects, the alkaline material can be a strong base, such as calcium oxide, calcium hydroxide or a combination thereof. Without being bound by theory, it is believed that when the pill comprises a strong base, the pill has a dual effect because it can hydrolyze the acetate portion in the cellulose acetate tow and break the glycosidic bond.

[0100] Enzyme material can comprise esterase, cellulase, beta-glucosidase or its combination.In some respects, esterase is lipase.When comprising enzyme material without any alkaline material, esterase is used.When also comprising enzyme material except alkaline material, then can use cellulase, beta-glucosidase or the combination of cellulase, beta-glucosidase and esterase.

[0101] Alkaline material and / or enzyme material can be included in pill in many ways.For example, alkaline material and / or enzyme material can constitute whole pill, can be included in pill together with other materials, and / or can be included in the coating on pill.In some respects, pill can include the coating containing alkaline material and / or enzyme material.Alkaline material and / or enzyme material can only be present in the coating or can be present in both coating and pill inside.Alkaline material and / or enzyme material can also be present in the concentrated part of pill or can be dispersed in whole pill.When coating contains alkaline material, enzyme material or its combination, alkaline material, enzyme material or its combination can be dispersed in the coating part between coating surface and pill inside, that is, alkaline material, enzyme material or combination are not facing environment.In other respects, alkaline material, enzyme material or its combination can be spread over coating, but then provide extra coating around the coated pill, so that alkaline material, enzyme material or its combination are not exposed to environment, otherwise decomposition may be activated prematurely.

[0102] In order to control the activation of the alkaline material and / or enzyme material in the pill, the pill can include an outermost coating, such as a coating based on a material other than cellulose acetate. The coating can be water-soluble, such as having a water solubility of at least 0.01 g / 100 mL at 25°C, such as at least 0.1 g / 100 mL at 25°C, at least 0.5 g / 100 mL at 25°C, at least 1.0 g / 100 mL at 25°C. In some aspects, the coating material includes gelatin, polyethylene glycol, polylactic acid, polycaprolactone, polyvinyl pyrrolidone, polyvinyl alcohol, or a combination thereof. In other aspects, the coating can include oligosaccharides, monosaccharides, polyhydroxyalkanoates, or a combination thereof. The coating material may contain less than 1 wt.% of cellulose acetate, less than 0.1 wt.% of cellulose acetate, or may be free of cellulose acetate. The thickness of the coating can be from 0.1 to 100 μm, e.g., from 0.5 to 80 μm, from 1 to 75 μm, or from 5 to 50 μm. The thickness around the pill can be uniform, or can have varying thicknesses. In some aspects, the water solubility of the alkaline material can be less than the water solubility of the coating, e.g., at least 5%, at least 10%, or at least 25%. In some aspects, the outermost coating can be free of cellulose acetate, while the inner coating does contain cellulose acetate.

[0103] Pill, including any coating thereon, can comprise from 1 to 99wt.%, for example from 5 to 99wt.%, from 10 to 90wt.% or from 25 to 75wt.% alkaline material. Pill can also contain other components, including filler, flavoring, sweetener, emulsifier, disintegration aid, humectant, insect repellent (buggering agent), and mixture thereof. These other components can constitute the remaining weight of pill individually or in combination with alkaline material and / or enzyme material as described herein. In some aspects, other components of preparation can be artificial or can be obtained or derived from herbal medicine or biological source. Exemplary types of components that may be incorporated into one or more formulations according to the present invention include salts, such as sodium chloride, potassium chloride, sodium citrate, potassium citrate, sodium acetate, potassium acetate; natural sweeteners, such as fructose, sucrose, glucose, maltose, vanillin, ethyl vanillin glycoside, mannose, galactose, and lactose; artificial sweeteners, such as sucralose, saccharin, aspartame, acesulfame K, and neotame; organic and inorganic fillers, such as cereals, processed cereals, expanded cereals, maltodextrin, dextrose, calcium carbonate, calcium phosphate, corn starch, lactose, sugar alcohols (such as isomalt, mannitol, xylitol or sorbitol), finely divided cellulose, and vegetable proteins; binders, such as povidone, sodium carboxymethylcellulose and other modified Cellulose type binders, sodium alginate, xanthan gum, starch-based binders, gum arabic, gellan gum, and lecithin; gelling agents such as fish gelatin pH adjusters or buffers such as metal hydroxides, including alkaline metal hydroxides such as sodium hydroxide and potassium hydroxide, and other alkali metal buffers such as metal carbonates, including potassium carbonate or sodium carbonate, or metal bicarbonates such as sodium bicarbonate; emulsifiers; dyes and pigments; humectants such as glycerol and propylene glycol; preservatives such as potassium sorbate; syrups such as honey and high fructose corn syrup; disintegration aids such as microcrystalline cellulose, cross-linked sodium carboxymethyl cellulose, cross-linked polyvinylpyrrolidone, sodium starch glycolate, and pregelatinized corn starch; flavorings and mixtures of flavorings, antioxidants, and mixtures thereof. Exemplary component types may include those described in, for example, U.S. Publication No. 2010 / 0291245, which is incorporated herein by reference.

[0104] In some aspects, alkaline material can be included in the coating of pill.For example, coating can include at least 1wt.%, such as at least 5wt.%, at least 10wt.%, at least 20wt.%, at least 30wt.%, at least 40wt.% or at least 50wt.% alkaline material based on the gross weight of coating. The weight ratio range of coating material and alkaline material can be from 10:1 to 1:99, such as from 5:1 to 1:99, from 3:1 to 1:99, from 1:1 to 1:99 or from 1:1 to 1:50. Alkaline material can be included in the pill itself.In some aspects, pill and coating all include alkaline material.In other aspects, any one in pill or coating contains alkaline material.

[0105] When included in the pill itself, it means that in addition to in the coating, the pill may also contain at least 1 wt.%, such as at least 5 wt.%, at least 10 wt.%, at least 20 wt.%, at least 30 wt.%, at least 40 wt.%, or at least 50 wt.% of alkaline material based on the total weight of the coating.

[0106] In some aspects, the enzyme material can be included in the coating of the pill. For example, the coating can include at least 1wt.%, such as at least 5wt.%, at least 10wt.%, at least 20wt.%, at least 30wt.%, at least 40wt.%, or at least 50wt.% of the enzyme material based on the total weight of the coating. The weight ratio of the coating material to the enzyme material can range from 10:1 to 1:99, such as from 5:1 to 1:99, from 3:1 to 1:99, from 1:1 to 1:99, or from 1:1 to 1:50.

[0107] When included in the pellet itself, it means that in addition to in the coating, the pellet may also contain at least 1 wt.%, such as at least 5 wt.%, at least 10 wt.%, at least 20 wt.%, at least 30 wt.%, at least 40 wt.%, or at least 50 wt.% of enzyme material based on the total weight of the coating.

[0108] The enzyme material may be contained in the pill itself. In some aspects, both the pill and the coating contain the enzyme material. In other aspects, either the pill or the coating contains the enzyme material. In aspects where the pill does not contain alkaline materials, the enzyme material includes an esterase to deacetylate the cellulose acetate. In aspects where the pill contains alkaline materials, the pill may include an esterase, a cellulase, a glucosidase, or a combination thereof. An esterase may be included to deacetylate or assist in deacetylation of the cellulose acetate, and once the DS of the cellulose acetate is less than 1.3, a cellulase, a glucosidase, or a combination thereof may be included to degrade the cellulose acetate.

[0109] In other aspects, the pills may contain an alkaline material or an esterase in a coating on the pills, and then may contain a different enzyme material in the pills. Such different enzyme materials, such as cellulases, glucosidases, or combinations thereof, may be coated and included in the pills. The coating of the enzyme material may be the same or different from the coating of the pills, and is referred to herein as a second coating.

[0110] In some aspects, the pellets deacetylate the cellulose acetate tow by at least 20% in 20 days or less, at least 30% in 20 days or less, at least 40% in 20 days or less, at least 50% in 20 days or less, or at least 60% in 20 days or less. In some aspects, the pellets deacetylate the cellulose acetate tow by at least 20% in 10 days or less, at least 30% in 10 days or less, at least 40% in 10 days or less, at least 50% in 10 days or less, at least 60% in 10 days or less, at least 80% in 10 days or less, or at least 90% in 10 days or less. In some aspects, the pellets deacetylate cellulose acetate tow by at least 20% in 30 days or less, at least 40% in 30 days or less, at least 50% in 30 days or less, at least 60% in 30 days or less, at least 70% in 30 days or less, or at least 80% in 30 days or less. As used herein, deacetylation is measured by using ion chromatography with a conductivity detector that directly measures acetate anions in aqueous solution.

[0111] Coating or part of cellulose ester products

[0112] As described herein, alkaline materials, enzyme materials, or combinations thereof may be included in cellulose ester products as coatings or by forming a portion of the product from alkaline materials, enzyme materials, or combinations thereof. The coating may cover a portion of the cellulose ester product or the entire product, such as at least 0.1% of the product in terms of the surface area covered, such as at least 0.5%, at least 1%, at least 2%, at least 3%, at least 4%, or at least 5%. The thickness of the coating may be from 0.1 μm to 1 mm, such as from 0.2 μm to 1 mm, from 0.3 μm to 1 mm, from 0.4 μm to 1 mm, from 0.5 μm to 1 mm, or any range therebetween. The coating may contain the materials described in the above pill section, including a first coating comprising an alkaline material and a second coating comprising an enzyme material, wherein the second coating is oriented between the alkaline material coating and the cellulose ester product.

[0113] Alternatively, or in addition to the coating, a portion of the cellulose ester article can actually be formed by an alkaline material, an enzyme material, or a combination thereof. As with the coating and the pill, the size, weight, and composition of this portion can be selected based on many factors. In some aspects, more than one portion of the cellulose ester article can be formed by an alkaline material, an enzyme material, or a combination thereof. These portions can be randomly spaced or can be evenly spaced.

[0114] The present disclosure will be better understood in light of the following non-limiting examples.

[0115] Examples

[0116] Example 1

[0117] In order to determine the deacetylation rate of cellulose acetate according to various catalytic materials, cellulose acetate tow with a DS of 2.5 was prepared and formed into rods. These rods also contained 8wt.% of triacetin as a plasticizer. The weight of each rod was about 0.15 grams. Each rod was then placed in about 4 milliliters of deionized water. In all samples except comparative sample A, about 50 milligrams of catalytic material were added to the water as shown below. After 3 days and after 38 days, the pH was measured. The deacetylation percentage was measured by taking out a sample of the cellulose acetate tow and using high performance liquid chromatography (HPLC). The results are shown below.

[0118]

[0119]

[0120]

[0121] The rate of deacetylation is important because, as described herein, the acetyl moieties of cellulose acetate must be replaced with hydroxyl moieties in order for natural degradation to occur. As shown above, Comparative Sample A, which does not include a catalytic material, had only a 9.93% degree of deacetylation after 38 days. Comparative Sample B, which includes citric acid as a catalytic material, unexpectedly performed worse than Comparative Sample A. Samples 1 and 2 performed well and showed more deacetylation at day 4 than Comparative Samples A and B at day 38. Samples 3 and 4 had the best performance, achieving complete or nearly complete deacetylation by day 3. Although the degrees of deacetylation for Samples 3 and 4 included values ​​above 100%, it is believed that these values ​​are due to the assumption of 8 wt.% triacetin.

[0122] Example 2

[0123] To determine the deacetylation rate of cellulose acetate in smoked cigarette filters based on various materials, cellulose acetate tow rods were prepared as above, except that they had a filter rod weight of about 0.24 grams. The plasticizer and catalyst were the same as in Example 1. The alkaline material was also the same as in Example 1. The measurements were made as in Example 1. The results are shown below.

[0124]

[0125]

[0126] Similar to the results shown above, pellets containing alkaline materials produced unexpectedly and unexpectedly increased deacetylation rates compared to Comparative Samples D, E, and F.

[0127] Example 3

[0128] The samples were prepared as above, except that the alkaline material was embedded in the cigarette filter.

[0129]

[0130] Example 4

[0131] To test the total degradation, a smoked cigarette was provided, with the paper removed. The alkaline material was placed in the filter and then allowed to biodegrade. ISO 19679 (2016) was followed, except that river water was used instead of seawater. The results were Figure 1 The results are shown in Figure 2 and show that calcium oxide and calcium hydroxide consume almost twice as much carbon dioxide as when no alkaline material is included. Based on the slope of the line, the percentage of carbon dioxide consumed relative to cellulose is 82.39% for calcium hydroxide, 83.10% for calcium oxide, and 42.55% for the control without any alkaline material added.

[0132] Example 5

[0133] To test the total degradation, a smoked cigarette was provided from which the paper was removed. The enzyme material was placed in the filter and then biodegraded. ISO 19679 (2016) was followed, except that river water in a 250 mL Erlenmeyer flask (actually 30 g of river sediment per 70 g of river water) and about 30 mg of sample were used instead of seawater. The released carbon dioxide was absorbed by 3 mL of 0.5 N KOH solution and determined by titration with 0.05 M HCL solution. The percentage of biodegradation was obtained by the ratio of the released carbon dioxide to the theoretical carbon dioxide. The results are in Figure 2, and shows that the % biodegradation of samples S5-S8 was greater over a shorter period of time (in days) compared to the reference (cotton linters) and control (untreated filter).

[0134] Example 6

[0135] The samples were prepared and tested as described above, but using 30 g of marine sediment per 70 g of artificial seawater (rather than river water). Figure 3 , and shows that the % biodegradation of samples S9-S12 was greater in a shorter period of time (in days) compared to the reference (cotton linters) and control (untreated filter).

[0136] Example 7

[0137] Samples were prepared and tested using river water as described in Example 5 and compared to untreated filters containing different amounts of enzyme. Figure 4 As shown, over time (in days), the % biodegradation increases as the amount of enzyme contained in the untreated filter increases.

[0138] Example

[0139] Embodiment 1: A degradable cellulose ester article comprising cellulose ester, wherein at least a portion of the article comprises an alkaline material, an enzyme material, or a combination thereof.

[0140] Embodiment 2: The degradable cellulose ester product as described in Embodiment 1, wherein the cellulose ester comprises cellulose acetate, cellulose butyrate, cellulose propionate, cellulose triacetate, cellulose acetate propionate, cellulose acetate butyrate, cellulose propionate butyrate, cellulose nitrate, cellulose sulfate, cellulose phthalate, and combinations thereof. Embodiment 3: The degradable cellulose ester product as described in any one of Embodiments 1-2, wherein the alkaline material, enzyme material, or a combination thereof is provided as a coating on the cellulose ester product.

[0141] Embodiment 4: The degradable cellulose ester product according to any one of embodiments 1-2, wherein the alkaline material, enzyme material, or a combination thereof is provided as pellets within the degradable cellulose ester product.

[0142] Embodiment 5: The degradable cellulose ester product as described in Embodiment 4, wherein the pellets include a coating.

[0143] Embodiment 6: The degradable cellulose ester product according to any one of embodiments 1 to 5, wherein the pH of the alkaline material is at least 7.4, preferably at least 7.6.

[0144] Embodiment 7: The degradable cellulose ester product as described in any one of embodiments 1-6, wherein the alkaline material comprises at least one of calcium oxide, calcium hydroxide, magnesium hydroxide, magnesium oxide, or a combination thereof.

[0145] Embodiment 8: The degradable cellulose ester product according to any one of embodiments 4-7, wherein the pellets comprise an alkaline material and an enzyme material, and wherein the enzyme material comprises esterase, cellulase, glucosidase, or a combination thereof.

[0146] Embodiment 9: The degradable cellulose ester product as described in any one of embodiments 4-8, wherein the enzyme material comprises esterase.

[0147] Embodiment 10: The degradable cellulose ester product as described in any one of embodiments 5-9, wherein the coating of the pellets comprises the alkaline material.

[0148] Embodiment 11: The degradable cellulose ester product according to any one of embodiments 5 to 10, wherein the pellets contain the enzyme material, and wherein the enzyme material is coated with a second coating material.

[0149] Embodiment 12: The degradable cellulose ester product according to any one of embodiments 4-11, wherein the pellets contain an enzyme material, the enzyme material comprising esterase and at least one of cellulase, glucosidase, or a combination thereof.

[0150] Embodiment 13: The degradable cellulose ester product according to any one of embodiments 5 to 12, wherein the water solubility of the coating material at 25°C is at least 0.01 g / 100 mL.

[0151] Embodiment 14: The degradable cellulose ester product as described in any one of embodiments 5-13, wherein the coating material comprises gelatin, polyethylene glycol, polylactic acid, polycaprolactone, polyvinyl pyrrolidone, polyvinyl alcohol, or a combination thereof.

[0152] Embodiment 15: The degradable cellulose ester product as described in any one of embodiments 5-14, wherein the coating material comprises oligosaccharides, monosaccharides, polyhydroxyalkanoates, or a combination thereof.

[0153] Embodiment 16: The degradable cellulose ester product as described in any one of embodiments 5-15, wherein the coating material does not contain cellulose acetate.

[0154] Embodiment 17: The degradable cellulose ester product as described in any one of embodiments 11-16, wherein the second coating material comprises gelatin, polyethylene glycol, polylactic acid, polycaprolactone, or a combination thereof.

[0155] Embodiment 18: The degradable cellulose ester product according to any one of embodiments 11 to 16, wherein the second coating material comprises oligosaccharides, monosaccharides, and / or polyhydroxyalkanoates.

[0156] Embodiment 19: A degradable cellulose ester product as described in any one of embodiments 4-18, wherein the pellets, when exposed to water, deacetylate the expanded cellulose acetate tow by at least 20%, preferably at least 30%, and more preferably at least 60% in 20 days or less.

[0157] Embodiment 20: The degradable cellulose ester product as described in any one of embodiments 1-2, wherein the alkaline material, enzyme material, or a combination thereof is provided as: a liquid capsule, a coating on the cellulose ester product, a pellet within the degradable cellulose ester product, or a coating on the pellet within the degradable cellulose ester product.

[0158] Embodiment 21: A degradable cigarette filter, comprising:

[0159] A filter element comprising expanded cellulose acetate tow, wherein the cellulose acetate has a degree of substitution (DS) greater than 1.3; pellets dispersed in the expanded cellulose acetate tow; and a plug wrap at least partially surrounding the filter element; wherein the pellets comprise a coating and at least one of an alkaline material, an enzyme material, or a combination thereof, and wherein the pellets, when exposed to water, deacetylate the expanded cellulose acetate tow by at least 10% in 20 days or less.

[0160] Embodiment 22: The filter of Embodiment 21, wherein the water solubility of the alkaline material is less than the water solubility of the coating.

[0161] Embodiment 23: The filter of any one of embodiments 21-22, wherein the pH of the alkaline material is at least 7.4, preferably at least 7.6.

[0162] Embodiment 24: A filter as described in any of Embodiments 21-23, wherein the alkaline material includes at least one of calcium oxide, calcium hydroxide, magnesium hydroxide, magnesium oxide, or a combination thereof.

[0163] Embodiment 25: The filter of any of embodiments 21-24, wherein the pellet comprises an alkaline material and an enzyme material, and wherein the enzyme material comprises an esterase, a cellulase, a glucosidase, or a combination thereof.

[0164] Embodiment 26: The filter of any of Embodiments 21-25, wherein the enzyme material comprises an esterase.

[0165] Embodiment 27: The filter of any one of Embodiments 21-26, wherein the coating has a thickness of from 0.1 to 100 μm.

[0166] Embodiment 28: A filter as described in any of embodiments 21-27, wherein the size of the pellets is from 1 to 10 mm at their largest diameter.

[0167] Embodiment 29: A filter as described in any of embodiments 21-28, wherein the coating of the pellets comprises the alkaline material.

[0168] Embodiment 30: The filter of Embodiment 21, wherein the pellet comprises the enzyme material, and wherein the enzyme material is coated with a second coating material.

[0169] Embodiment 31: The filter of any of Embodiments 21-30, wherein the pellet comprises an enzyme material comprising an esterase and at least one of a cellulase, a glucosidase, or a combination thereof.

[0170] Embodiment 32: The filter of any one of Embodiments 21-31, wherein the coating material has a water solubility of at least 0.01 g / 100 mL at 25°C.

[0171] Embodiment 33: A filter as described in any one of embodiments 21-32, wherein the coating material comprises gelatin, polyethylene glycol, polylactic acid, polycaprolactone, polyvinyl pyrrolidone, polyvinyl alcohol, or a combination thereof.

[0172] Embodiment 34: The filter of any one of embodiments 21-33, wherein the coating material comprises an oligosaccharide, a monosaccharide, a polyhydroxyalkanoate, or a combination thereof.

[0173] Embodiment 35: A filter as described in any of Embodiments 21-34, wherein the coating material does not contain cellulose acetate.

[0174] Embodiment 36: A filter as described in Embodiment 30, wherein the second coating material comprises gelatin, polyethylene glycol, polylactic acid, polycaprolactone, polyvinyl pyrrolidone, polyvinyl alcohol or a combination thereof.

[0175] Embodiment 37: The filter of Embodiment 30, wherein the second coating material comprises oligosaccharides, monosaccharides, and / or polyhydroxyalkanoates.

[0176] Embodiment 38: A filter as described in any of embodiments 21-37, wherein the pellets, when exposed to water, deacetylate the expanded cellulose acetate tow by at least 20%, preferably at least 30%, and more preferably at least 60% in 20 days or less.

[0177] Embodiment 39: A degradable cellulose acetate tow, wherein the degree of substitution of the cellulose acetate tow is greater than 1.3, and wherein the cellulose acetate tow further comprises pellets dispersed in the cellulose acetate tow, wherein the pellets comprise a coating and at least one of an alkaline material, an enzyme material, or a combination thereof, and wherein the pellets, when exposed to water, deacetylate the cellulose acetate tow by at least 10% in 20 days or less.

[0178] Embodiment 40: A method for forming a degradable cellulose acetate tow, the method comprising: a) providing a cellulose acetate tow having a degree of substitution greater than 1.3;

[0179] b) dispersing pellets in the cellulose acetate tow, wherein the pellets comprise at least one of an alkaline material, and an enzyme material, or a combination thereof, wherein the pellets, when exposed to water, deacetylate the cellulose acetate tow by at least 10% in 20 days or less.

[0180] Embodiment 41: The method of embodiment 40, wherein the pellets hydrolyze the acetate moieties within the cellulose acetate tow and cleave the glycosidic bonds.

[0181] Embodiment 42: A method for forming a degradable cellulose ester article, the method comprising: a) providing a cellulose ester having a degree of substitution greater than 1.3; b) dispersing pellets in the cellulose ester, wherein the pellets comprise at least one of an alkaline material, and an enzyme material, or a combination thereof, wherein the pellets, when exposed to water, deacetylate the cellulose ester by at least 10% in 20 days or less.

[0182] Embodiment 43: A method for forming a degradable cellulose ester product, the method comprising: a) forming a cellulose ester product from a cellulose ester having a degree of substitution greater than 1.3; and b) providing a coating on at least a portion of the cellulose ester product, wherein the coating comprises an alkaline material, an enzyme material, or a combination thereof.

[0183] Example 44: A method for forming a degradable cellulose ester product, the method comprising: a) providing a cellulose ester having a degree of substitution greater than 1.3; b) providing an alkaline material, an enzyme material, or a combination thereof; and c) forming the cellulose ester product by at least one of extrusion, thermoforming, blow molding, 3D printing, injection molding, and a combination thereof.

[0184] Embodiment 45: A degradable cellulose ester article comprising cellulose ester and liquid capsules, wherein the liquid capsules comprise an alkaline material, an enzyme material, or a combination thereof.

[0185] Although the present invention has been described in detail, modifications within the spirit and scope of the present invention will be apparent to those skilled in the art. It should be understood that the various aspects of the present invention and the various embodiments and portions of the various features described above and / or in the appended claims may be combined or interchanged in whole or in part. In the above description of the various embodiments, those embodiments that mention another embodiment may be appropriately combined with other embodiments, as understood by those of ordinary skill in the art. In addition, it will be understood by those of ordinary skill in the art that the above description is by way of example only and is not intended to limit the present invention.

Claims

1. A degradable cellulose ester article comprising cellulose ester, wherein at least a portion of the article comprises an alkaline material, an enzyme material, or a combination thereof.

2. The degradable cellulose ester product according to claim 1, wherein: The cellulose esters include cellulose acetate, cellulose butyrate, cellulose propionate, cellulose triacetate, cellulose acetate propionate, cellulose acetate butyrate, cellulose propionate butyrate, cellulose nitrate, cellulose sulfate, cellulose phthalate, and combinations thereof.

3. The degradable cellulose ester product according to claim 1, wherein: The alkaline material, enzyme material, or a combination thereof is provided as a liquid capsule, a coating on the cellulose ester preparation, a pellet within the degradable cellulose ester preparation, or a coating on a pellet within the degradable cellulose ester preparation.

4. The degradable cellulose ester product according to claim 1, wherein: The alkaline material includes at least one of calcium oxide, calcium hydroxide, magnesium hydroxide, magnesium oxide, or a combination thereof.

5. The degradable cellulose ester product according to claim 1, wherein: The pellets comprise an alkaline material and an enzyme material, and wherein the enzyme material comprises an esterase, a cellulase, a glucosidase, or a combination thereof.

6. The degradable cellulose ester product according to claim 1, wherein: The enzyme material comprises an esterase.

7. The degradable cellulose ester product according to claim 3, wherein: The coating of the pellets comprises the alkaline material.

8. The degradable cellulose ester product according to claim 3, wherein: The pellets contain the enzyme material, and wherein the enzyme material is coated with a second coating material.

9. The degradable cellulose ester product according to claim 3, wherein: The pellets contain an enzyme material including an esterase and at least one of a cellulase, a glucosidase, or a combination thereof.

10. The degradable cellulose ester product according to claim 3, wherein: The coating material has a water solubility of at least 0.01 g / 100 mL at 25°C.

11. The degradable cellulose ester product according to claim 3, wherein: The coating material includes gelatin, polyethylene glycol, polylactic acid, polycaprolactone, polyvinyl pyrrolidone, polyvinyl alcohol, or a combination thereof.

12. The degradable cellulose ester product according to claim 3, wherein: The coating material includes oligosaccharides, monosaccharides, polyhydroxyalkanoates, or combinations thereof.

13. The degradable cellulose ester product according to any one of claims 3, wherein The coating material does not contain cellulose acetate.

14. A degradable cigarette filter, comprising: A filter element comprising bulked cellulose acetate tow, wherein the cellulose acetate has a degree of substitution (DS) greater than 1.3; pellets dispersed in said expanded cellulose acetate tow; and a plug wrap at least partially surrounding the filter element; wherein the pellets comprise a coating and at least one of an alkaline material, an enzyme material, or a combination thereof, and wherein the pellets, when exposed to water, deacetylate the bulked cellulose acetate tow by at least 10% in 20 days or less.

15. The filter according to claim 14, wherein: The water solubility of the alkaline material is less than the water solubility of the coating.

16. The filter according to claim 15, wherein: The alkaline material includes at least one of calcium oxide, calcium hydroxide, magnesium hydroxide, magnesium oxide, or a combination thereof.

17. The filter according to claim 15, wherein: The pellets comprise an alkaline material and an enzyme material, and wherein the enzyme material comprises an esterase, a cellulase, a glucosidase, or a combination thereof.

18. The filter according to claim 15, wherein: The enzyme material comprises an esterase.

19. The filter according to claim 15, wherein: The thickness of the coating is from 0.1 to 100 μm.

20. A degradable cellulose acetate tow, wherein the cellulose acetate tow has a degree of substitution greater than 1.3, and wherein the cellulose acetate tow further comprises pellets dispersed in the cellulose acetate tow, wherein the pellets comprise a coating and at least one of an alkaline material, an enzyme material, or a combination thereof, and wherein the pellets, when exposed to water, deacetylate the cellulose acetate tow by at least 10% in 20 days or less.

Citation Information

Patent Citations

  • Disintegrable capsule, manufacturing method for same, and smoking device containing said disintegrable capsule

    US10015984B2

  • Degradable cigarette filter

    US20090151738A1

  • Soft, chewable and orally dissolvable and / or disintegrable products

    US20100291245A1

  • Methods for Synthesizing Acylated Cellulose Through Instillation of an Acidic Catalyst

    US20130096297A1

  • High Denier Per Filament and Low Total Denier Tow Bands

    US20130115452A1

Cited By

  • High-salt-resistant corrosion inhibition type nano imbibition agent as well as preparation method and application thereof

    CN121362574A